Atp2b2 Oblivion heterozygous mutation causes progressive vestibular dysfunction in mice - LIU Yiqing; JIN Chenxi; FENG Baoyi; CHENG Zhenzhe; SUN Yilin; ZHENG Xiaofei; DONG Tingting; WU Hao; TAO Yong (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2024)
Objective·To study the alterations in vestibular hair cell morphology and function of ATPase plasma membrane Ca2+ transporting 2 oblivion (Atp2b2 Oblivion) heterozygous mice at different ages.Methods·Atp2b2 Oblivion heterozygous male mice aged 2 months and 8 months were selected with ten in each kind and C57BL/6J wild-type mice with the same gender, age and number were selected as the control group. Expression patterns of ATP2B2 in vestibular hair cells and numbers of hair cells in the striola zone and the extra striola zone in the two groups of mice at different ages were observed and calculated respectively through immunofluorescence assay. Hair bundle structures were detected by scanning electron microscopy (SEM), and mitochondria and ribbon synapse structures were observed by transmission electron microscopy (TEM). Vestibular evoked potential (VsEP), vestibular evoked myogenic potential (VEMP), rotarod rod test, and balance beam test were adopted for the evaluation of vestibular functions.Results·ATP2B2 was mainly expressed in the hair bundle of vestibular hair cells in the two groups of mice. Hair cell numbers in the striola zone and the extra-striola zone did not exhibit any differences between Atp2b2 Oblivion heterozygous mutant mice and wild-type mice of 2-month-old and 8-month-old. No visible structural abnormality in the hair bundle could be seen through SEM. TEM results implied no morphological abnormality in mitochondria or ribbon synapses in the 2-month-old heterozygous mutant mice, while vacuolar degeneration was discovered in the mitochondria under the cuticular plate in the 8-month-old heterozygous mutant mice with the normal ribbon synapses and the normal mitochondria near the innervation site. VsEP and VEMP thresholds of 2-month-old and 8-month-old Atp2b2 Oblivion heterozygous mutant mice were significantly elevated compared with the wild-type mice. Analysis of VsEP waveform manifested prolonged P1 latency and declined P1N1 amplitude in heterozygous mutant mice (P<0.05). Results of rotarod rod test and balance beam test acquired from 2-month-old Atp2b2 Oblivion heterozygous mutant mice were not significantly different from the wild-type mice, while the ability of the mutant mice to accomplish the tests descended significantly at 8 months of age compared with the wild-type mice (P<0.05).Conclusion·Atp2b2 Oblivion heterozygous mutant mice showed defective vestibular electrophysiological function at 2 months old, and abnormalities in vestibule-related behaviors can be detected at 8 months old. The vestibular function of Atp2b2 Oblivion heterozygous mutant mice deteriorate progressively.